Advances in Environmental Geotechnics Proceedings of the International Symposium on Geoenvironmental Engineering in Hangzhou, China, September 8-10, 2009 - Chen, Yunmin.; Chen, Yunmin.; Tang, Xiaowu.; Tang, Xiaowu.; Zhan, Liangtong.; Zhan, Liangtong. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
"Advances in Environmental Geotechnics" presents the latest developments in this interdisciplinary field. The topics covered include basic and advanced theories for modeling of geoenvironmental phenomena, testing and monitoring for geoenvironmental engineering, municipal solid wastes and landfill engineering, sludge and dredged soils, geotechnical reuse of industrial wastes, contaminated land and remediation technology, applications of geosynthetics in geoenvironmental engineering, geoenvironmental risk assessment, management and sustainability, ecological techniques and case histories. This proceedings includes papers authored by core members of ISSMGE TC5 (International Society of Soil Mechanics and Geotechnical Engineering---Environmental Geotechnics) and geoenvironmental researchers from more than 20 countries and regions. It is a valuable reference for geoenvironmental and geotechnical engineers as well as civil engineers. Yunmin Chen, Xiaowu Tang, and Liangtong Zhan are Professors at the Department of Civil Engineering of Zhejiang University, China.